Peran Inovasi Produk dan Orientasi Pasar terhadap Kinerja Koperasi Konsumen Puri Nirwana, Cibinong - Lubban Anwari Alhamidi (Neolectura, 2021)
This associative research was conducted to determine the effect of market orientation and product innovation on the performance of the Puri Nirwana Consumer Cooperative, Cibinong. The population in this study were 100 active members of the cooperative and used a saturated sample (census) technique. This research uses SPSS 24.00 analysis. Methods of data collection in this study using interviews and questionnaires. The hypothesis was tested by simple regression using path analysis techniques and Sobel test. The results of hypothesis testing indicate that all proposed hypotheses are accepted. market orientation has a positive and significant effect on product innovation orientation, product innovation has a positive and significant effect on performance, market orientation has a positive and significant effect on performance and product innovation is able to mediate the effect of market orientation on the performance of the Puri Nirwana Consumer Cooperative, Cibinong significantly.